2021
DOI: 10.1111/asj.13531
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding Bacillus subtilis on rumen fermentation, blood metabolites, nutrient digestibility, and energy and nitrogen balances in non‐lactating crossbred cows

Abstract: The utilization of probiotics in livestock diets is increasing because it can result in improved productivity. Bacillus spp. are gram-positive spore-forming bacteria that are resistant to heat, cold, acid, and digestive enzymes (Carlin, 2011;Casula & Cutting, 2002). Although they cannot colonize the intestinal tracts of animals, they can have beneficial effects on productivity. Various studies have been conducted to clarify the effects of Bacillus spp. supplements. When supplied in pig feed, Bacillus subtilis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Sallam et al ( 18 ) observed improved N balance by 22% when animals were fed a diet supplemented with probiotics. Moreover, Kawauchi et al ( 58 ) observed that feeding cows on a diet supplemented with B. subtilis did not affect the amounts of N loss in the feces or urine or retained N. Increased N retention in body tissues may explain the increased daily gain in animals fed additives. Lack of differences in ruminal ammonia-N, blood urea-N concentrations and N excreted revealed an improved utilization of nutrients ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sallam et al ( 18 ) observed improved N balance by 22% when animals were fed a diet supplemented with probiotics. Moreover, Kawauchi et al ( 58 ) observed that feeding cows on a diet supplemented with B. subtilis did not affect the amounts of N loss in the feces or urine or retained N. Increased N retention in body tissues may explain the increased daily gain in animals fed additives. Lack of differences in ruminal ammonia-N, blood urea-N concentrations and N excreted revealed an improved utilization of nutrients ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics did not impact ammonia N, indicating minimal effects on dietary protein breakdown and digestion, and the uptake of ammonia by bacteria ( 58 ). However, BAC increased CP digestibility indicating increased uptake of ammonia by bacteria and increased microbial protein in the rumen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacillus licheniformis, Bacillus subtilis, Prevotella bryantii [41] Increase in growth performance, improving weight gain, feed conversion efficiency in weaning calves Bifidobacterium, Lactobacillus, and Enterococcus [42] In Egypt, some trials were performed to explore the beneficial effects of probiotics additives on ruminant performance, productivity and health; Hassan et al, (2020) [43] investigated the mixing of two different forms (powder or liquid) of Ruminococcus flavefaciens with concentrate feed that presented to group of Barki lambs for75 days. They mentioned that the addition of examined probiotics resulted in a significant increase in nearly all of the dry matter digestibility coefficients, average daily gain and nutrient digestibility compared to the control group.…”
Section: Polygastric Animalsmentioning
confidence: 99%